Cell Membrane and Electron Transfer Engineering for Improved Synthesis of Menaquinone-7 in Bacillus subtilis - Cui, Shixiu; Xia, Hongzhi; Chen, Taichi; Gu, Yang; Lv, Xueqin; Liu, Yanfeng; Li, Jianghua; Du, Guocheng; Liu, Long (iScience, 2020)
The formation of biofilm facilitates the synthesis of valuable natural product menaquinone-7 (MK-7) in static culture of Bacillus subtilis, whereas the essential role and mechanism of biofilm in MK-7 synthesis have not been revealed. Herein, comparative transcriptomics show that the formation of biofilm affected MK-7 synthesis by changing the transcription levels of signal receptor (BSU02010), transmembrane transporter (BSU29340, BSU03070), and signal transduction (BSU02630). Moreover, we also found that oxalate decarboxylase OxdC has an important effect on electron generation and MK-7 synthesis, when the transcriptional level of NADH dehydrogenase decreases in static culture. Our results revealed that cell membrane and electron transfer are important factors in promoting MK-7 synthesis. [Display omitted] •Transcriptome analysis shows the relationship between biofilm and MK-7 synthesis•Electron transfer significantly affects the synthesis of MK-7•Oxalate decarboxylase OxdC plays a role in electron generation and MK-7 synthesis Metabolic Engineering; Biotechnology; Microbial Biotechnology